2018
DOI: 10.1051/medsci/201834f119
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depression and blood cytokine levels in lung cancer patients

Abstract: > Objective: To study the correlation between depression and blood cytokine levels in lung cancer patients. Methods: 92 patients with advanced lung cancer were evaluated for depression using the scoring index of depression self-rating scale. Lack of depression (n=24), mild depression (n=45), and moderate depression (n=23) were found in the cohort. Meanwhile, 40 healthy subjects were selected as the control group. The levels of IL-10, IL-6, IL-8, and TNF-α in each group were detected by sandwich enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In 2001, Musselman et al first reported that cancer patients with depression had significantly higher plasma IL-6 levels than healthy control subjects and cancer patients without depression [60]. Similar findings were demonstrated that the depression state was positively correlated with IL-6 levels in patients with cancer [61], lung cancer [62], colorectal cancer [63], pancreatic cancer [64], breast cancer [65,66], metastatic cancer [67], advanced cancer [68] and ovarian cancer [69]. One study investigated IL-6 level changes in six months following primary treatment in ovarian cancer patients [70].…”
Section: Il-6 In Physical Diseases Associated With Depressionmentioning
confidence: 74%
“…In 2001, Musselman et al first reported that cancer patients with depression had significantly higher plasma IL-6 levels than healthy control subjects and cancer patients without depression [60]. Similar findings were demonstrated that the depression state was positively correlated with IL-6 levels in patients with cancer [61], lung cancer [62], colorectal cancer [63], pancreatic cancer [64], breast cancer [65,66], metastatic cancer [67], advanced cancer [68] and ovarian cancer [69]. One study investigated IL-6 level changes in six months following primary treatment in ovarian cancer patients [70].…”
Section: Il-6 In Physical Diseases Associated With Depressionmentioning
confidence: 74%
“…Recent studies have correlated depression, a very common symptom in PH patients, to increased levels of circulating pro-inflammatory cytokines and microglial activation (48,62,92,128). Pro-inflammatory cytokines positively correlated with depression score index in a study of 92 patients diagnosed with lung cancer (62).…”
Section: 21mentioning
confidence: 98%
“…COVID-19 is usually accompanied by an elevation of numerous bioactive factors such as IL-1β, TNF-α, IL-2, IL-7, IL-8, IL-9, IL-17 G-CSF, interferon (IFN)-γ, XXC-10, CCL-2 CCL-3, CCL-4, and especially IL-6, which is produced predominantly by macrophages [110,111]. The severe and frequently fatal character of the disease is characterised by a high level of IL-6 and CRP in the blood or plasma of the patients [112][113][114][115]. IL-6, in collaboration with other factors, influences the endothelial cells of lung capillaries, increasing their permeability for serum proteins and improving the transmigration of inflammatory cells [116].…”
Section: Covid-19 and Il-6mentioning
confidence: 99%